Detection and removal of “smacking” artefacts from lector speech records - Jaskuła, Marek; Perużyńska, Hanna (Archives of Acoustics, 2007)
In the paper, analysis of “smacking” artefacts, introduced to the speech signal by a lector,was shown. A working algorithm to reduce amount of smacks in the waveform was presented.The algorithm performs detection of distortions in the time domain using differentiation ofthe signal. The removal routine is based on Dicrete Wavelet Transform (DWT) and InverseDiscrete Wavelet Transform (IDWT).